Integration of Internet of Things (IoT) and Artificial Intelligence for Campus Education: A Case Study of Energy Management and Security - Putri, Desfita Eka; Krisnawati, Nova; Adhicandra, Iwan; Sitopu, Joni Wilson (Civiliza Publishing, Indonesia., 2025)
The rapid advancement of digital technology has transformed educational institutions, presenting opportunities to enhance campus energy management and security. This research investigates the integration of the Internet of Things (IoT) and Artificial Intelligence (AI) to improve energy efficiency and security systems in a university campus setting. The study employed a qualitative research method using a case study approach, which included interviews, observations, and document analysis conducted over six months. Data analysis followed a thematic approach to identify patterns in energy consumption, security threats, and system performance. The results demonstrated that integrating IoT and AI reduced energy consumption by 20% through automated controls and predictive analytics, while security incidents decreased by 30% with improved response times by 40%. The study confirms previous theoretical energy conservation and security enhancement models while highlighting practical challenges such as sensor connectivity issues and staff training. This research contributes to the field by demonstrating the synergistic potential of combining IoT and AI for holistic campus management. Future research should explore integrating renewable energy sources with IoT technologies to enhance environmental sustainability while maintaining campus security. The findings offer valuable insights for educational institutions adopting smart campus technologies for improved operational efficiency and safety.